Bounce back harder: resilience and reinvention of entrepreneurship - Muhamad Irfan Haziq Rahmad,; Ainnur Batrisyia Aminurrashid,; Nur Ain Mustafa,; Amirul Hakim Nor Azam, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study aims to investigate how entrepreneurs deal with business challenges. Specifically, the objectives of this study are twofold; first, to examine how entrepreneurs acquire resilience in facing business challenges, and second, to how the entrepreneurs rebuild their businesses. The study proposed to conduct a literature review analysis as data collection to investigate the inquiries. The study attempts to focus on psychological attributes, social support networks, and organizational capacities and the function of resilience in minimizing the impact of exogenous shocks on entrepreneurial initiatives. In addition, the study will analyze literature on reinvention, where a business's ability to pivot in response to changing market conditions, technological breakthroughs, or other external variables. It is expected that the findings could contribute to providing an in-depth understanding of how entrepreneurs deal with business challenges. The findings would be useful for entrepreneurs to develop skills and training in dealing with business challenges. Overall, the goal of this paper is to contribute to a better understanding of the dynamic and ever-changing character of entrepreneurship, as well as the role of resilience and reinvention in achieving entrepreneurial achievement.